Politics of precarity: neoliberal academia under austerity measures and authoritarian threat. (1st December 2019) - Loher, David; Strasser, Sabine
Abstract : In recent years, precarity has become the norm rather than an exception in contemporary European academia. This special issue on politics of precarity examines the economic, social and political crisis‐effects of the neoliberal turn in academia. It analyses how austerity measures and authoritarian politics have led to a proliferation of precarity among, mostly young, scholars.